Global Nollywood : The Transnational Dimensions of an African Video Film Industry - Okome, Onookome; Krings, Matthias, 1967 September 26- (Book collections on Project MUSE., 2013)
Global Nollywood considers this first truly African cinema beyond its Nigerian origins. In 15 lively essays, this volume traces the engagement of the Nigerian video film industry with the African continent and the rest of the world. Topics such as Nollywood as a theoretical construct, the development of a new, critical film language, and Nollywood's transformation outside of Nigeria reveal the broader implications of this film form as it travels and develops. Highlighting controversies surrounding commodification, globalization, and the development of the film industry on a wider scale, this volume gives sustained attention to Nollywood as a uniquely African cultural production.